THE REFLECTION OF TRANSITIONAL SOCIETY OF MYTILENE AT THE END OF THE ARCHAIC PERIOD (8TH – 5TH CENTURY B.C.) A STUDY ON SAPPHO’S “ODE TO ANAKTORIA” - Lydia Kanelli Kyvelou Kokkaliari; Bani Sudardi (Analisa: Journal of Social Science and Religion, 2017)
This article discusses Sappho’s “Ode to Anaktoria” (fragment 16) poem as a ‘marginal’ product of an aristocratic intellectual in the transitional society of Mytilene at the end of the Archaic Period (8th-5th century B.C.). The research method is a kind of media analysis. The mean of “media” in this paper related to “A means by which something is communicated or expressed” It is laso relate to the intervening substance through which sensory impressions are conveyed or physical forces are transmitted. Media also means as a substance in which an organism lives or is cultured. On the other hand, media is a material or form used by an artist, composer, or writer; We interpreted Ode to Anaktoria  in the means as the terms of media above. Sappho (born 610, died 570 B.C.) is a renowned Greek lyric poetess and musician and is greatly admired in all ages for the beauty of her writing style. Plato’s 16th epigram dedicated to her reads “Some say there are nine Muses; but they should stop to think. Look at Sappho of Lesbos; she makes a tenth”. Sappho is additionally ranked among the Nine Lyric Poets esteemed by the scholars of Hellenistic Alexandria as worthy of critical study. “Ode to Anaktoria” is read through the historic-political concept of hegemony as suggested by Gramsci. In this view, the moment of “hegemony” or of cultural leadership is systematically upgraded precisely in opposition to the mechanistic and fatalistic concepts of economism. Sappho’s fragment 16 does not only indicate defiance to androcentric (epic) categories; she suggests nonnormative, thus new, ways of contemplating life (lyric).